Application of Neural Network and Virtual Reality Technology in Digital Video Effects - Liao Jiang (International Transactions on Electrical Energy Systems)
With the continuous innovation of technology, digital technology is more and more widely used in the production of TV shows and movies and plays an important role. The effective application of digital video effects technology can enhance the visual effects of the overall TV and film works and improve the quality of the works. After the use of digital special effects in film and television production, people see more exquisite film and television pictures, but today’s technology is not enough to meet people’s growing demand for film and television pictures. This paper applied neural network and virtual reality technology to the production process of digital video effects and conducted a comparative experiment with the digital video effects produced by using the current technology. The special effects were evaluated in four aspects: image fidelity, sound distortion, picture fluency, and production efficiency. The experimental results show that after applying neural network and virtual reality technologies, the image fidelity of digital video effects is increased by 6.74%, the sound distortion is reduced by 7.69%, the picture fluency is increased by 6.89%, and the production efficiency is increased by 7.91%. Applying the neural network and virtual reality technology can improve the quality and efficiency of digital video special effects production.